FORMULA DAN KARAKTERISTIK KELISANAN KABHANTI GAMBUSU PADA MASYARAKAT MUNA - La Sudu (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2025)
The creation of kabhanti gambusu is based on formulas and orality. Each kabhanti gambusu performer has mastered ready-to-use formulaic patterns that facilitate and enhance the creative process during each performance. This study aims to explain the formulas and characteristics of orality in kabhanti gambusu among the Mun community. This type of research is field research using a qualitative descriptive method. Data collection was conducted through observation, interviews, note-taking, and recording. The results show that a good storyteller who wants to learn the technique of storytelling or singing from their teacher does not memorize the text; instead, they focus on orality. The storyteller recreates the utterances they have learned. In this context, performing kabhanti gambusu does not involve rote memorization but rather the recollection of most of the formulaic patterns. These formulaic forms consist of repetitions of sounds, syllables, words, and phrases.